2017
DOI: 10.1111/codi.13855
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and fate of the defunctioning stoma in patients with anal cancer: a regional experience following the ACT II trial

Abstract: The tumour features that are indications for defunctioning as advised by the UK IMRT guidelines are associated with a poorer overall outcome, and these stomas are less likely to be reversed. The majority of stomas, however, were formed for anterior tumours without infiltration into the vagina and were more likely to be successfully reversed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 16 publications
1
5
0
6
Order By: Relevance
“…Previous studies have documented divergent results regarding the indications for and reversal rates of pretreatment stomas. The need for a colostomy ranges from 9% to 51%, and the reversal rates range from 5% to 48% 9–13 . Case series considering distinct numbers of patients with advanced tumors, less strict indications and cultural aspects may help to explain this discrepancy.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies have documented divergent results regarding the indications for and reversal rates of pretreatment stomas. The need for a colostomy ranges from 9% to 51%, and the reversal rates range from 5% to 48% 9–13 . Case series considering distinct numbers of patients with advanced tumors, less strict indications and cultural aspects may help to explain this discrepancy.…”
Section: Discussionmentioning
confidence: 99%
“…Common symptoms of anal SCC, such as anal pain or mild bleeding, usually improve with the initiation of CRT and are not considered a formal indication for colostomy. Poynter et al 12 evaluated the rationale for pretreatment stomas and concluded that patients with fecal incontinence, obstruction, or rectovaginal fistula were at higher risk of requiring a permanent stoma, while patients with less precise indications, such as anteriorly located tumors in women without clinically evident fistulas, were more likely to undergo reversal surgery. Of the 30 female patients with anteriorly located tumors, none of them developed a new fistula during CRT, so the need for a diversion does not seem justified.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations